Exploring entrepreneurial intentions of students: international perspective - Celina Sołek-Borowska; Haruthai Numprasertchai (International Entrepreneurship Review, 2018)
The purpose of the paper is firstly to identify the entrepreneurial intentions of students from two countries: Poland and Thailand.  Secondly to assess the contribution of these universities in enhancing entrepreneurial intentions amongst students through entrepreneurship education and training programs. The Polish students represent Warsaw School of Economics (SGH) whilst  Thai students represent Kasetsart University (KU). Paper questionnaires were used to survey students studying at both Universities. Participation in the survey was voluntary. The study conﬁrms that entrepreneurial education can positively reinforce student attitudes towards an entrepreneurial career choice within countries like Poland and Thailand. It is also apparent that students at SGH had more exposure to informal education than those from KU. The research ﬁndings are of interest to academia and policy makers. The study suggests that entrepreneurial attitudes amongst Polish and Thai students can be inﬂuenced by exposure to entrepreneurship education. Overall, the study indicates a need for entrepreneurship education, at programme and course levels, to nurture entrepreneurship among students in Poland and Thailand. This research may contribute to the growing body of knowledge that has begun to explore intentions of individuals for self-employment.